Barriers to Transition From Pediatric to Adult Care: A Systematic Review. (28th November 2017) - Gray, Wendy N; Schaefer, Megan R; Resmini-Rawlinson, Alana; Wagoner, Scott T
Abstract: Objective: Transition research in each disease group is developing in its own "silo." A comprehensive review of barriers to transition within and across chronic illness groups is needed to facilitate information sharing and larger-scale efforts to overcome barriers and improve patient care. This study systematically reviews and identifies the barriers to transition from pediatric to adult care across pediatric illness populations. Methods: Medline, CINAHL, PsychINFO, Social Services Abstracts, Web of Science, and the Cochrane library databases were searched. Peer-reviewed English articles presenting original data on barriers to transition to adult care, focused on a specific pediatric chronic illness population, and conducted in the United States were included. Study design, population, and barriers were extracted. Barriers were categorized according to the Socioecological Model of Adolescent/Young Adult Readiness to Transition. Articles were evaluated for study quality. Results: Fifty-seven articles were included. The most common barriers to transition fell within the "Relationships" domain (e.g., difficulties letting go of long-standing relationships with pediatric providers) followed by "Access/Insurance" (e.g., difficulty accessing/finding qualified practitioners, insurance issues), and "Beliefs/Expectations" (e.g., negative beliefs about adult care). Barriers related to "Knowledge" (e.g., limited patient/caregiver knowledge about medication/illness and the transition process) and "Skills/Efficacy" (e.g., lack of self-management skills) were also common. While relationship barriers were commonly reported by all, some barriers varied by transfer status (pre- vs. posttransfer). Conclusions: Each chronic illness group experiences illness-specific challenges but certain barriers transcend chronic illness populations. Suggestions to overcome these barriers are provided.